Fatigue and brittle fracture of carbon steel of gas and oil pipelines - Maruschak, Pavlo; Poberezhny, Lyubomyr; Pyrig, Taras (Transport, 2013)
The areas of low frequency and corrosion fatigue for basic metal and welding joints of oil and gas pipelines have been determined on the basis of corrosion-fatigue test results. The most dangerous diapasons of the operation loadings were also determined. The present work also proposes the methodical approaches to the survivability prediction.First Published Online: 11 Oct 2013